The Degree to which Teachers of the Second Cycle of Basic Education apply the Dimensions of Educational Security from their Perspective (Journal of the College of Education for Women, 2023)
Recently, many undesirable behaviors have spread in our daily life in society, whether from the teacher to his students or from the students among themselves as a result of the absence of educational security and the decline in the role of socialization institutions in general and the school in particular in training students on values. Positive social, Thus, the study was descriptive. Theory by adopting information about educational security and the nature of teachers’ practice thereof. The descriptive analytical approach was used and a questionnaire was administered to (48) male and female teachers at this stage. Therefore, the aim of the current research is to identify the degree to which teachers practice the dimensions of educational security, based on the theoretical framework and previous studies prepared in this regard, and accordingly, the curriculum was used, it came in first place with an arithmetic average of (2.26 and after education Dialogue learners ranked second with a arithmetical average of (2.19( while it came after providing a positive, supportive place for learners in the third and final rank with a low arithmetical average of (1.56). There were differences in the average scores of male and female sample members applying the dimensions of educational security in favor of female teachers in the three dimensions where the arithmetic mean for the dimension of using modern technologies is (48.40), for the dimension of educating learners in dialogue (75.35), and for the dimension of providing a positive, supportive place for learners (38.33). Differences were found. In the teachers’ scores on the questionnaire in favor of a diploma. qualification or above in the three dimensions, there were no differences in the teachers’ scores on the questionnaire in favor of 10 years of experience or more in the three dimensions.